2014
DOI: 10.1177/1368430214550342
|View full text |Cite
|
Sign up to set email alerts
|

Interracial friendship and the trajectory of prominority attitudes: Assessing intergroup contact theory

Abstract: We analyze the trajectory of racial attitude change among White university students, over a 4-year time period, representing an advancement over previous studies’ use of longitudinal designs alone to test the causal ordering and nature of the relationship between contact and attitudes. Adding to the literature on intergroup friendships, we examined the impact of two types of intergroup contact (interracial friendships and neighborhood racial context) on two types of racial attitudes: attitudes supportive of af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 33 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Nonetheless, closeness to people targeted by prejudice was a more consistent predictor of reported participation in protests for racial justice than more general, everyday forms of intergroup contact. These trends parallel other work suggesting that cross-race friendships may encourage White people to become more likely to support programs that would benefit the racially disadvantaged (Northcutt Bohmert & DeMaris, 2015) and to participate in collective action for racial justice (Selvanathan et al, 2017); and that White women may be more inclined to engage in civil rights activism the more that such social and political issues are imbued with personal meaning (Duncan & Stewart, 2007). Close relationships with members of targeted groups may provide a pathway for White women to become more psychologically invested in the welfare and interests of other disadvantaged groups (see Tropp & Barlow, 2018;Wright et al, 2005).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nonetheless, closeness to people targeted by prejudice was a more consistent predictor of reported participation in protests for racial justice than more general, everyday forms of intergroup contact. These trends parallel other work suggesting that cross-race friendships may encourage White people to become more likely to support programs that would benefit the racially disadvantaged (Northcutt Bohmert & DeMaris, 2015) and to participate in collective action for racial justice (Selvanathan et al, 2017); and that White women may be more inclined to engage in civil rights activism the more that such social and political issues are imbued with personal meaning (Duncan & Stewart, 2007). Close relationships with members of targeted groups may provide a pathway for White women to become more psychologically invested in the welfare and interests of other disadvantaged groups (see Tropp & Barlow, 2018;Wright et al, 2005).…”
Section: Discussionsupporting
confidence: 74%
“…Other scholars have suggested that meaningful intergroup contact experiences of advantaged group members can nurture a sense of psychological investment in the welfare of other groups, such that they may come to care about the experiences and interests of groups beyond their own (Tropp & Barlow, 2018;Wright, Brody, & Aron, 2005). Among White Americans, greater numbers of interracial friendships predicted greater support for affirmative action over time (Northcutt Bohmert & DeMaris, 2015), and having in-depth conversations with a person of color can enhance their willingness to acknowledge their own racial privilege (Nordstrom, 2015). In addition, the more close contacts White people reported having with Black people, the more they empathized with what Black people experience; greater empathy was closely linked to greater anger regarding the injustices Black people face and greater support for, and participation in, collective action for racial justice (Selvanathan, Techakesari, Tropp, & Barlow, 2017).…”
Section: Protests Among the Advantaged: The Role Of Social Relationsmentioning
confidence: 99%
“…For instance, in the South African context, Whites who report close, friendly contact with Blacks report greater support for policies that would enhance educational and economic opportunities for Black South Africans (Dixon et al, 2010). In the United States, longitudinal research shows that greater numbers of interracial friendships predict Whites’ greater support for affirmative action over time (Northcutt Bohmert & DeMaris, 2015), and having in-depth conversations with a person of color can enhance Whites’ willingness to acknowledge racial privilege (Nordstrom, 2015). In some of our own work (Selvanathan, Techakesari, Tropp, & Barlow, 2017), we have found that Whites’ contact with Black Americans predicts greater willingness to take action to challenge racial inequality.…”
Section: Intergroup Contact: Fostering Acknowledgment and Action In Rmentioning
confidence: 99%
“…This line of thinking is consistent with intergroup contact theory, or the idea that forming positive, interdependent relationships with multiple members of an outgroup leads to more positive attitudes of that community. It is one of the most effective and applicable methods of improving crosscultural relations; for example, Bohmert and DeMaris (2015) found that having more interracial friendships is strongly associated with more positive racial attitudes. Then, in order to reduce internal racial biases, cooperative bonds must be formed with many people of various different backgrounds.…”
Section: Discussionmentioning
confidence: 99%